A prominence eruption from the Sun to the Parker Solar Probe with multi-spacecraft observations - Niembro, Tatiana; Seaton, Daniel B.; Hess, Phillip; Berghmans, David; Andretta, Vincenzo; Reeves, Katharine K.; Riley, Pete; Stevens, Michael L.; Landini, Federico; Sasso, Clementina; Verbeeck, Cis; Susino, Roberto; et al. (Frontiers in Astronomy and Space Sciences, 2023)
In the early hours of 2021 April 25, the Solar Probe Cup on board Parker Solar Probe registered the passage of a solar wind structure characterized by a clear and constant He2+/H+ density ratio above 6% during three hours. The He2+ contribution remained present but fainting and intermittent within a twelve-hour window. Solar Orbiter and Parker Solar Probe were in nearly perfect quadrature, allowing for optimal observing configuration in which the material impacting the Parker Solar Probe was in the Solar Orbiter plane of the sky and visible off the limb. In this work, we report the journey of the helium-enriched plasma structure from the Sun to the Parker Solar Probe by combining multi-spacecraft remote-sensing and in situ measurements. We identify an erupting prominence as the likely source, behind the Sun relative to the Earth, but visible to multiple instruments on both the Solar-Terrestrial Relations Observatory-A and Solar Orbiter. The associated CME was also observed by coronagraphs and heliospheric imagers from both spacecrafts before reaching the Parker Solar Probe at 46 R⊙, 8 h after the spacecraft registered a crossing of the heliospheric current sheet. Except for extraordinary helium enhancement, the CME showed ordinary plasma signatures and a complex magnetic field with an overall strength enhancement. The images from the Wide-field Imager for Solar Probe (WISPR) aboard Parker Solar Probe show a structure entering the field of view a few hours before the in situ crossing, followed by repetitive transient structures that may be the result of flying through the CME body. We believe this to be the first example of a CME being imaged by WISPR directly before and during being detected in situ. This study highlights the potential of combining the Parker Solar Probe in situ measurements in the inner heliosphere with simultaneous remote-sensing observations in (near) quadrature from other spacecrafts.